2016
DOI: 10.1093/eurheartj/ehw027
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous closure of patent foramen ovale in migraine with aura, a randomized controlled trial

Abstract: In patients with refractory migraine with aura and PFO, PFO closure did not reduce overall monthly migraine days.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
113
1
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 177 publications
(121 citation statements)
references
References 24 publications
3
113
1
4
Order By: Relevance
“…The answer depends on how the result will affect treatment. In three randomized clinical trials of PFO closure in persons with MA, there was no evidence for decrease in frequency, intensity, or severity of migraine, and it is therefore not routinely recommended as a treatment option . Closure of PFO, might, however, still be considered in the setting of recurrent migraine‐like transient neurological events despite use of antiplatelet therapy, and MRI abnormalities, including white matter T2 hyperintensities and stroke‐like lesions.…”
Section: Implications For Diagnosis and Treatmentmentioning
confidence: 99%
“…The answer depends on how the result will affect treatment. In three randomized clinical trials of PFO closure in persons with MA, there was no evidence for decrease in frequency, intensity, or severity of migraine, and it is therefore not routinely recommended as a treatment option . Closure of PFO, might, however, still be considered in the setting of recurrent migraine‐like transient neurological events despite use of antiplatelet therapy, and MRI abnormalities, including white matter T2 hyperintensities and stroke‐like lesions.…”
Section: Implications For Diagnosis and Treatmentmentioning
confidence: 99%
“…Indeed, data presented at cardiology conferences in 2006, 2014, and 2015 representing the MIST, PREMIUM, and PRIMA trials offered negative results regarding the utility of PFO closure for the treatment of migraine222324. The present (EASTFORM) study evaluated the long-term impact of PFO closure on migraine in a real-world setting of patients enrolled and included in a continuous registry at a single centre in China, and importantly addressed ethnic differences in the efficacy and safety of PFO closure for migraine.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, this unequal and greater effect on migraine with aura is likely a true effect of PFO closure. There was only one vascular major complication and one transient atrial fibrillation reported from the interventional procedure [34]. …”
Section: Discussionmentioning
confidence: 99%